Data Envelopment Analysis application in the evaluation of efficient measurement instruments - Sanchez Velasco, José (IJRDO-Journal of Applied Science, 2019)
The following article incorporates operational efficiency analysis in the context of dimensional metrology with a focus on technology selection- the objective is to evaluate measurement technologies under similar conditions and according to the physical characteristics of the instruments. The document proposes a selection of variables that allow comparing the attributes of the measurement process in different instruments for a specific piece – in such a way that the methodology shown can be applied to pieces with similar characteristics. The instruments are within the field of dimensional metrology and are representative of those commonly used in the industrial and the academic sector in the country. The contribution of this work consists of carrying a statistical tool normally used in managing organizational operations towards a technical environment such as dimensional metrology. The results present an opportunity for future research by combining the fields of metrology and efficiency analysis.